Enhancing Students' Listening Skills: Leveraging Digital Media Through Lampung Barat's Cultural Heritage - Abdulloh; Surastina; Sudarmaji; Wiratno, Purna; Damiri, Adenan (IJLHE: International Journal of Language, Humanities, and Education, 2024)
This research explores the impact of integrating digital media with local cultural elements to improve listening skills among students. The study distinguishes listening as an active process that requires engagement and comprehension, contrasting it with mere hearing. Employing a Classroom Action Research (CAR) methodology, the study involved planning, implementation, and reflection phases with 35 second-semester students at STKIP PGRI Bandar Lampung. Data collection methods included tests, interviews, and observations, with triangulation ensuring the validity of the findings. The results indicate a significant improvement in students' listening skills, evidenced by an increase in average listening comprehension scores from 71.75 to 80.65 over two research cycles. This improvement is attributed to the effective integration of visual digital media with cultural content from Lampung Barat. Despite initial challenges related to student focus and engagement, the study demonstrates that cultural understanding is crucial for effective listening and that modern technology can enhance this process. Success was evaluated based on student participation, comprehension, and achievement of Minimum Completion Criteria (MCC), with a notable number of students meeting these metrics in Cycle II. The research concludes that combining local cultural elements with digital technology enriches the learning experience, leading to substantial improvements in listening proficiency and overall student outcomes. This approach offers promising opportunities for curriculum development and pedagogical innovation, suggesting that such integration could be beneficial across various academic disciplines to create more engaging and relevant educational environments